2021
DOI: 10.1007/s11695-021-05571-y
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Patient Adherence to Multivitamin Intake After Bariatric Surgery: a Multicentre Survey Study from the Patient’s Perspective

Abstract: Purpose Lifelong multivitamin supplementation is recommended to prevent nutritional deficiencies. Despite this advice, deficiencies are common which may be due to poor adherence to MVS intake. The aim of this study was to identify which factors affect patient adherence to Multivitamin Supplement (MVS) intake after bariatric surgery. Materials and Methods A 42-item questionnaire was sent to 15,424 patients from four Dutch bariatric center. In total, 4975 patients wanted to participate of which 361 patients were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 24 publications
2
14
0
Order By: Relevance
“…This is in line with other research on adherence to supplementation regimes after bariatric surgery with (self-reported) compliance rates ranging between 37 and 93% up to 5 years post-surgery [7,14,15,[17][18][19][20]. Besides commonly reported barriers as gastro-intestinal side effects, bad taste/smell/size, and high cost [13,15,19], some patients believe that their diet provides sufficient micronutrients and therefore do not feel the need to use MVS [15,19]. This is concerning as we found that about 66% of the non-users in this study presented with one or more nutrient deficiencies during follow-up, whereas this was only about 30% in the groups that used a specialized MVS.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This is in line with other research on adherence to supplementation regimes after bariatric surgery with (self-reported) compliance rates ranging between 37 and 93% up to 5 years post-surgery [7,14,15,[17][18][19][20]. Besides commonly reported barriers as gastro-intestinal side effects, bad taste/smell/size, and high cost [13,15,19], some patients believe that their diet provides sufficient micronutrients and therefore do not feel the need to use MVS [15,19]. This is concerning as we found that about 66% of the non-users in this study presented with one or more nutrient deficiencies during follow-up, whereas this was only about 30% in the groups that used a specialized MVS.…”
Section: Discussionsupporting
confidence: 91%
“…Over time, supplement use varied and adherence to MVS declined with less than half of the participants consistently using the same MVS throughout follow-up and the percentage of non-users increasing up to 24% at 3 years after SG. This is in line with other research on adherence to supplementation regimes after bariatric surgery with (self-reported) compliance rates ranging between 37 and 93% up to 5 years post-surgery [7,14,15,[17][18][19][20]. Besides commonly reported barriers as gastro-intestinal side effects, bad taste/smell/size, and high cost [13,15,19], some patients believe that their diet provides sufficient micronutrients and therefore do not feel the need to use MVS [15,19].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Identifying individual barriers is necessary to improve adherence. In a recent study by Smelt et al, the most common reasons for poor adherence or non-persistence were difficulty in remembering to use supplements, gastrointestinal side effects, unpleasant taste or smell, high costs, and the absence of vitamin deficiencies in blood tests [17].…”
Section: Discussionmentioning
confidence: 99%